Music Sharing as a Computer Supported Collaborative Application - Brown, Barry A. T.; Sellen, Abigail; Geelhoed, Erik (Proceedings of ECSCW 2001, Bonn, Germany, 2001)
New computer applications, such as the infamous “Napster” system enable the sharing of music over the Internet, with limited communication around this sharing activity. This paper discusses the use and opportunities for these music sharing technologies using interviews with users of both conventional and new music sharing technologies. The data show that music sharing is a practice that is richly linked with other social activities. New music is often discovered through friends, by listening to music together, or in the form of compilation tapes. In these environments, sharing music is a natural activity. With music sharing over the Internet, however, much of this social context is removed. This suggests opportunities to turn music sharing into a more collaborative and community-related activity. These opportunities are explored with the “Music Buddy”, a system for browsing others’ music collections without infringing the copyright of artists.